DEVELOPMENT OF ENZYME-LINKAGE IMMUNOSORBENT ASSAY AGAINST TYPE B OF CLOSTRIDIUM BOTULINUM: A PRELIMINARY STUDY - S. N. Depamede; D. Kisworo (Journal of the Indonesian Tropical Animal Agriculture, 2011)
Clostridium botulinum neurotoxin (BoNTs) is one of the causes of economic loss in the livestock industry. This economic loss would be as a direct result when animals poisoned by BoNTs or indirectly when the livestock products are contaminated by BoNTs, which end up with the products are banned by authority. Therefore a routine surveillance of BoNTs in the farm and in livestock product processing industry is urgently needed. One of the most relatively quick and accurate methods to perform a routine detection of the presence of BoNTs is enzyme-linkage immunosorbant assay (ELISA). In this article we describe the results of the development of ELISA, using polyclonal antibodies against BoNTs-B produced locally. Antibodies were generated from six Balb/c mice with standard immunological methods. Mice were immunized three times for a period of 8 weeks with a commercial type B Clostridium botulinum toxoid at a dose of 100 ng per mouse per injection. The resulting antibody was purified by a combination of ammonium sulfate precipitation 50% (w/v) technique and a protein A column method. The results of this preliminary study indicated that the developed ELISA method capable of detecting type B Clostridium botulinum toxin up to 1.0 ng/ml.